2002
DOI: 10.1063/1.1473683
|View full text |Cite
|
Sign up to set email alerts
|

Manufacture of specific structure of aluminum-doped zinc oxide films by patterning the substrate surface

Abstract: (0001)-oriented aluminum-doped zinc oxide films were prepared using a magnetron sputtering technique. High-resolution transmission-electron- microscopic images show that the oriented grains nucleate directly on the substrate surface and grow with equal lateral dimensions through the film thickness. A surface-energy-driven self-texture mechanism was proposed on the basis of process modes. A method for manufacturing specific film structure by patterning the substrate surface is tested and discussed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(49 citation statements)
references
References 20 publications
(11 reference statements)
2
46
0
1
Order By: Relevance
“…This result indicates that the films are composed of a wurtzite type hexagonal structure and have a preferential orientation of caxis normal to the substrate plane. It is well known that ZnO films consist of columnar grains grown with the c-axis orientation [27]. Therefore, this result indicates that the columnar-structured IZO thin films with vertical direction grown at pulse frequency of 30 kHz have highly c-axis crystallites to the substrate.…”
Section: Resultsmentioning
confidence: 77%
“…This result indicates that the films are composed of a wurtzite type hexagonal structure and have a preferential orientation of caxis normal to the substrate plane. It is well known that ZnO films consist of columnar grains grown with the c-axis orientation [27]. Therefore, this result indicates that the columnar-structured IZO thin films with vertical direction grown at pulse frequency of 30 kHz have highly c-axis crystallites to the substrate.…”
Section: Resultsmentioning
confidence: 77%
“…Moreover, it has been observed that ͑0002͒ lattice fringes along the substrate plane immediately appear at the interface between the substrate and the film; a similar result has been also reported in the case of relatively thick films. 8 These results provide us with strong evidence that, even at a thickness of only 30 nm, the film is composed of the equiaxed columnar grains grown from the initial stage of film deposition.…”
mentioning
confidence: 67%
“…The surface stresses for most materials are of the same order of magnitude as the corresponding surface energy values [29]. For ZnO, f 1 and f 2 are of the order of 2 N/m [32]. Figure 8(b) shows the approximate magnitude of the internal stress as a function of size.…”
Section: Mechanical Response and Effect Of Surface Stressmentioning
confidence: 95%